ANALISIS PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SUSU MURNI FRESH MILACK (Suatu Kasus pada Konsumen di Resto & Cafe Fresh Milack Kecamatan Cikole, Kota Sukabumi) - Ani Rani; Dety Sukmawati; Euis Dasipah; Nendah Siti Permana (Universitas Galuh, 2023)
This study aims to analyze how far individual characteristics and product characteristics influence the purchasing decision of Fresh Milack milk in Sukabumi City. The research method used in this paper is a quantitative method with descriptive analysis. Data was collected using direct interviews with respondents who were in the field using a questionnaire. The type of quantitative method used in this research is Path Analysis. This method analyzes consumer decisions in purchasing fresh milk based on individual characteristics and product characteristics. The results showed that individual characteristics and product characteristics influenced purchasing decisions on Fresh Milack milk. This means that when individual characteristics and product characteristics are diverse, it will result in an increase in the decision to purchase Fresh Milack milk in Sukabumi city.